Alternative pathway of cell death in Drosophila mediated by NF-κB transcription factor Relish - Chinchore, Yashodhan (National Academy of Sciences, 2012)
Photoreceptor cell death accompanying many retinal degenerative disorders results in irreversible loss of vision in humans. However, the precise molecular pathway that executes cell death is not known. Our results from a Drosophila model of retinal degeneration corroborate previously reported findings that the developmental apoptotic pathway is not involved in photoreceptor cell demise. By undertaking a candidate gene approach, we find that players involved in the immune response against Gram-negative bacteria are involved in retinal degeneration. Here, we report that the NF-κB transcription factor Relish regulates neuronal cell death. Retinal degeneration is prevented in genetic backgrounds that block Relish activation. We also report that the N-terminal domain of Relish encodes unique toxic functions. These data uncover a unique molecular pathway of retinal degeneration in Drosophila and identify a previously unknown function of NF-κB signaling in cell death.